Developing Communicative Competence Through Task-Based Language Teaching - Novita Nurmayanti (Rahis Cendekia Indonesia, 2025)
This study investigates the role of Task-Based Language Teaching (TBLT) in developing communicative competence among English as a Foreign Language (EFL) learners in an authentic classroom setting. Motivated by the persistent gap between traditional, form-focused instruction and learners’ limited communicative ability, the study employed a qualitative descriptive design involving classroom observations, audio–video recordings, interviews, and analysis of student task outputs. Findings indicate that TBLT substantially improved four major components of communicative competence: grammatical, discourse, sociolinguistic, and strategic competence. Students produced more accurate and varied structures, organized ideas more coherently, used socially appropriate expressions, and applied communication strategies to maintain interaction. Learners also reported increased motivation and confidence due to the meaningful, collaborative nature of tasks. Despite minor challenges such as uneven participation and vocabulary limitations, TBLT proved effective in promoting natural communication and active engagement. The study contributes to existing literature by demonstrating how TBLT operates in real classroom conditions and highlights its potential as a pedagogical approach for fostering holistic communicative competence in EFL contexts. Implications for classroom practice and suggestions for future research are also discussed.